An Upgraded Line List for Radiative Transitions between the B 2Σ+, A 2Π, and X 2Σ+ States of the CN Radical - S. V. Kozlov; V. A. Terashkevich; E. A. Pazyuk; A. V. Stolyarov; S. N. Yurchenko; J. Tennyson (The Astrophysical Journal Supplement Series)
The global mass-invariant coupled-channel deperturbation model of the B ^2 Σ ^+ , A ^2 Π, and X ^2 Σ ^+ states of the CN radical, which reproduces the overall rovibronic term values of mutually perturbed levels with almost spectroscopic accuracy, has been utilized to produce complete line lists of radiative transitions between the X ^2 Σ ^+ , B ^2 Σ ^+ , and A ^2 Π _1/2;3/2 states of CN isotopologues. The Einstein A emission coefficients generated for the A − X , B − X , and B − A transitions provide both lifetimes of the excited states as well as the B → A / X branching ratios. The ab initio permanent and transition dipole moments required are revisited within the framework of the multireference configuration interaction and of the averaged coupled-pair functional methods. An upgraded line list is provided in ExoMol format and employed to simulate intensity distribution into the high-temperature air plasma B → X and A → X spectra as well as in the rotational resolved B → X / A emission bands undergoing strong local B ∼ A ∼ X perturbations. A comparison with laboratory and astronomical spectra shows that the present line list significantly improves the treatment of both locally perturbed and highly excited rotational levels of the B ∼ A ∼ X complex.